Central banking in Latin America - Tamagna, Frank (Mexico : Centro de Estudios Monetarios Latinoamericanos, 1965)
This book is the first comprehensive presentation to the world at large of the central banks of Latin America, their history, organization, instruments, and policies.
osc 16/11/17
Loans
Keywords: Central Banking; Latin America